Identification of Fault Characteristics in the 2021 Ambarawa Swarm Earthquake Based On Focal Mechanism Analysis - Muhammad Rizal Ramadhani; Khafidh Nur Aziz; Budiarta (Universitas Negeri Surabaya, 2025)
Swarm earthquakes occur repeatedly within a certain time frame and occur in the same location with small earthquake strengths. A swarm earthquake occurred in the Ambarawa region of Central Java from October to November 2021. This research aims to determine the characteristics of new faults and the causes of fault activity in the 2021 Ambarawa earthquake. The method used in determining the characteristics of faults that cause swarm earthquakes is P wave first motion polarity recorded by the seismograph. A total of 7 earthquake data were analyzed using the P-wave first motion polarity method which produced compression/dilation data, azimuthal angle, and take-off angle. Analysis of the focal mechanism using compression/dilatation data, azimuthal angle, and take-off angle produces strike, dip, and rake values. The strike value in the focal mechanism of the 2021 Ambarawa earthquake ranges from N 54°, N 69°, N 168° to N 208°, and N 292°. The dip value in the focal mechanism of the 2021 Ambarawa earthquake has a value of 40° to 88°. The rake value in the focal mechanism of the 2021 Ambarawa earthquake has a negative value, indicating that it is a type of normal fault. The characteristics of the cause of the earthquake are caused by local faults in the Telomoyo Volcano area with normal fault types and shear faults. Local fault activity is indicated by the local pressure on the geothermal reservoir that flows magma fluid from the reservoir to the surface.